Penegakan Hukum terhadap Pidana Gelandangan Ditinjau dari Kebijakan Hukum Pidana - Ressy Rizki Utari; Ade Mahmud (UNISBA Press, 2022)
Abstract. It has been more than a century that the Indonesian Criminal Code has been in force. There have been more than four attempts to do so. However, the DPRD's hammer never knocks on the validity of the new Criminal Code. An attempt was also made in 2019. But instead it created a large wave of protests from many community groups. One of the articles that is also considered colonial and not pro to the people is Article 431 of the RKUHP. The article reads